The Role Of The Family As Supervisors Of Tuberculosis Medication Adherence - Kurniyawan, Enggal Hadi; Dwi Putri Maharani; Annisa Maulida Sabrina Fitriani; Zenitha Gelina Inachys; Wisnu Phambudi; Alfid Tri Afandi; Kholid Rosyidi Muhammad Nur (Rajaki of Tulip Medika Publisher, 2023)
Effective TB treatment involves consistent and timely administration of anti-TB drugs over a sufficiently long period. However, the problem of non-compliance with treatment is common and can result in treatment failure, spread of infection, and drug resistance. This study aims to examine the role of the family as a supervisor in monitoring medication adherence in TB patients. The literature search process in this literature review uses several databases, namely Google Scholar, Science Direct, and PubMed, with the publication year of 2018-2023. The results of this study are expected to provide better insight into the role of the family in supervising medication adherence in TB patients. With a better understanding of the factors influencing family roles, more effective steps can be taken to improve adherence to TB treatment. Our advice as writers is that anyone appointed as a supervisor of swallowing medicine, both nurses and patients' families, must carry out their duties in supervising patients taking medicine. This is because TB is a severe infectious disease, and the way to overcome it is by taking medication regularly and on time. Therefore, the role of drug-swallowing supervisors is needed in this case.